Top management involvement in key account management: a contingency model - Sun, Liang (Cranfield University, 2025)
Key Account Management (KAM) plays a strategic role in driving long-term customer value, yet its implementation remains challenging. While prior research recognises the importance of Top Management Involvement (TMI) in KAM, limited attention has been paid to what drives such involvement, how it manifests in practice, and how it is shaped by contextual contingencies. This study addresses these gaps through an abductive, multi-case research design involving seven organisations. It identifies 19 drivers of TMI, categorised along proactive–reactive and strategic–operational–individual dimensions. TMI is found to manifest across three behavioural domains: displayed commitment, decision- making approach, and interaction style. Importantly, the study demonstrates that structural, environmental, cognitive, and operational contingency factors moderate the relationship between TMI drivers and executive behaviours. These findings make theoretical contributions by refining and extending the conceptualisation of TMI, increasing our understanding of how personal traits influence TMI, illustrating its dynamic nature, and challenging the assumption that TMI is inherently beneficial to KAM performance. The study also offers practical insights for aligning executive involvement with KAM demands. It presents a set of ten role templates for executive involvement in KAM and concludes with limitations and suggestions for future research.
Prior, Daniel - Associate Supervisor
Keywords: Top Management Involvement (TMI); Key Account Management (KAM); Executive Decision-Making; Top Management Commitment; Behavioural Manifestation; Strategic Drivers; Reactive and Proactive Motivation; Contingency Factors; Upper Echelons Theory; Contextual Moderation